The Productive & Symbolic Functions of Management Control in the Chinese Hotel Industry: A Foucauldian Analysis - Wang, Jenny Jing (Auckland University of Technology, 2014)
Purpose – Thus, this thesis concerns, more generally, the mobilisation of accounting control mechanisms in organisations. The generic research question is: “How is accountability determined by measuring the productive and symbolic functions of staff labour in hotels in China”. The question is employed in the context of hotel organisations in China. Foucault’s concepts are employed to explain “how power is exercised” by managers to achieve performance and to maintain and improve Key Performance Indicators (KPIs). Power involves and promotes surveillance, examination/inspection, and discourse (what is said and what is unsaid) to provide managers with necessary power/knowledge to be effective decision makers (Foucault, 1980). The empirical illustrations are drawn from the author’s own experience as an employee of various Chinese hotels. Design/methodology/approach – the approach is ethnological employing the theories of Foucault on techniques of management control in the Chinese hotel industry. This is an empirical study based on the researcher’s own working experiences in several hotels within various positions. For this purpose, throughout her working experience a journal record was maintained of meetings and conversations with other staff. Ethnography as a research methodology, based on the researcher’s experiences is applied to this thesis. It is an approach that allows the researcher’s observations to develop the empirical elements necessary to meet the research questions posed in this thesis. Central to Foucault’s work is the question, “How power is exercised”, and, “What is its mechanism” (Foucault, 1980, p. 89). Power is exercised by mostly managers over staff to the end of what Foucault calls the triple function of labour (Foucault, 1980, p. 161). Foucault (1980) considers that accountability comprises three functions: the productive function - ensuring the work is done; the symbolic function - where staff are used to represent the organisation as in the Singapore Airlines ubiquitous “Singapore girl”; and the dressage or discipline function - where staff are enclosed and made uniform. It is the contention of this thesis that the dressage function is fundamental to maintain performance in the productive and symbolic functions. Findings – The surveillance, inspection and use of key performance indicators are control features familiar to accountants and auditors, whose function is to impose discipline and to enclose for accountability. By borrowing the disciplinary processes of accounting, managers can separate and enclose staff by function. With regard to the productive function record keeping and quantifying are necessary elements as are establishing performance indicators. The symbolic function has grown out of the productive function and the key performance indicators are harder to quantify as the function is more qualitative in application than quantitative. Nonetheless, to establish accountability, staff must be enclosed and made into efficient, uniform bodies aware of being always under the “gaze” of management. But, perhaps, control of the symbolic function owes most to the practices of audit, which relies on inspection, explanations and judgement before arriving at a qualitative evaluation. The overall contention of this thesis is that while both the productive and symbolic functions of staff are vital to financial performance in hotels, and the end of achieving financial key indicators is the driver for managers, it is the means of control of the symbolic function in the industry which has received little attention. Originality/value – the thesis ns how a technique developed by Foucault to explain the transition from the management of labour in medieval times to modern times is effected. Other accounting researchers have published landmark works using Foucault’s techniques to explain how accounting and accountability has been established in various industries. The originality of this thesis is to show how such techniques of disciplinary control relating to the productive and symbolic function of Chinese hotel staff becomes embedded.
Keywords: Foucauldian; Chinese hotel industry; Management control mechanism; Accountability